Microscale soft robotics : motivations, progress, and outlook - Kim, Jaeyoun (Springer, 2017)
This book presents the technological basics and applications of small-scale (mm to sub-mm in length-scales) soft robots and devices, written for researchers in both academia and industry. Author Jaeyoun Kim presents technological motivations, enabling factors, and examples in an inter-linked fashion, making it easy for readers to understand and explore how microscale soft robots are a solution to researchers in search of technological platforms for safe, human-friendly biomedical devices. A compact and timely introduction, this book summarizes not only the enabling factors for soft robots and MEMS devices, but also provides a survey of progress in the field and looks to the future in terms of the material, design, and application aspects this new technology demonstrates.
Keywords: Robotics.; Soft computing.; elektronické knihy; electronic books